2020
DOI: 10.1136/bmjopen-2019-033338
|View full text |Cite
|
Sign up to set email alerts
|

Hilly environment and physical activity among community-dwelling older adults in Japan: a cross-sectional study

Abstract: ObjectivesWe investigated whether a moderate-to-vigorous physical activity (MVPA) level and walking time were associated with a hilly environment in rural Japanese older adults.DesignCross-sectional study.SettingUnnan city, Ohnan and Okinoshima towns in Shimane, Japan.ParticipantsData were collected from 1115 adults from the Shimane CoHRE study, who were aged 60 years and older and living in rural Japan in 2012.MeasuresWe measured the total time spent on MVPA and walking using a Japanese short version of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…In Okinoshima town, where fishing is the main industry, the residents who lived in hilly areas had higher risk of physical inactivity. This result is inconsistent with a previous cross-sectional study that found that living in a hilly neighborhood was positively associated with PA among older Japanese adults [26]. The positive association between hilliness and PA was hypothesized to be due to beautiful scenery in a hilly environment encouraging older people to conduct recreational PA.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In Okinoshima town, where fishing is the main industry, the residents who lived in hilly areas had higher risk of physical inactivity. This result is inconsistent with a previous cross-sectional study that found that living in a hilly neighborhood was positively associated with PA among older Japanese adults [26]. The positive association between hilliness and PA was hypothesized to be due to beautiful scenery in a hilly environment encouraging older people to conduct recreational PA.…”
Section: Discussioncontrasting
confidence: 94%
“…Hilliness, bus stop density, intersection density, residential density, and distance to a community center were measured by geographic information systems (GIS). Land slope was used to assess the hilliness of the neighborhood, which has been reported to be associated with PA, weight change, and diabetes among older adults [26][27][28][29]. Bus stop density, intersection density, and residential density have also been reported to be associated with PA and health among older adults [15,16].…”
Section: Exposure Variables: Neighborhood Environmental Factorsmentioning
confidence: 99%
“…This longitudinal four-year follow-up study was conducted using data collected as part of the Shimane CoHRE Study in Shimane Prefecture. It targeted lifestyle-related diseases through the collection of data concerning medical history, lifestyle, and cognitive function during annual municipal health examinations [13][14][15][16].…”
Section: Design Setting and Samplementioning
confidence: 99%
“…Land slope was used to assess the hilliness of the neighborhood. Hilly neighborhoods have been reported to be associated with both higher and lower physical activity and weight gain in older adults [28][29][30]. The mean land slope was computed based on the Elevation and degree of Slope 5th Mesh Data obtained from the National Land Numerical Information (NLNI), which is publicly available GIS data administered by the National Land Information Division, National Spatial Planning, and Regional Policy Bureau of Japan.…”
Section: Exposure Variablesmentioning
confidence: 99%